ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONALDAN KOMUNIKASI INTERNAL TERHADAP MOTIVASI DANDAMPAKNYA PADA KINERJA KARYAWAN DI KANTOR PT.WASKITA KARYA DIVISI GEDUNG - Daniel Adanny Hardjuna; Ahmad Syarief (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
The purpose of this study is to describe and to know the effect of transformational leadership variables and internal communications on the motivation and impact on the performance of the employee in the office of PT. Waskita Karya building division. This study uses quantitative data research. Data collected by the research library (library research) and field research (field research). Data analysis method used in this research path analysis or assisted pathway analysis using the SPSS 22.0 software. Path Analysis (Path Analysis) is a technique used to examine the contribution (contribution) which is shown by the path coefficient on each path diagram of causal relationships between variables X1, X2 and X3 to Y and Z. impact on the findings it can be concluded is that the partial effect most strongly affect the performance of the employees are motivated, followed by internal communication and transformational leadership. Simultaneously transformational leadership and internal communication to motivate significant influence and so also with transformational leadership and internal communication through motivation on employee performance are significant and positive influence.